Gwendy's magic feather - Chizmar, Richard, 1965- (Cemetery Dance Publications, 2019)
With the mysterious reappearance of Richard Farris' button box, 37-year old Gwendy Peterson leaves Washington, D.C. for Castle Rock, Maine to help save two missing girls in the aftermath of a winter storm.